Approach to test program development for multilevel verification - Pavel Viktorovich Frolov (Труды Института системного программирования РАН, 2019)
Development of system-on-chips or network-on-chips requires verification of standalone units (peripherals and commutators) and a system as a whole. An approach to test development for verification of programmable standalone units is presented. The tests are written in C++ using a specific API to program the device-under-test (DUT) and the test environment. The API functions are implemented in the standard environment library; the specific implementation depends on the test environment structure: a standalone device, a device as a part of controllers block or a device as a part of the whole SoC. For system-level verification the test program is translated for execution on a general-purpose core of the verified SoC as well as the standard environment library. The testbench for unit-level verification consists of the environment library and the test linked to the testbench as a PLI-application, an adapter for the DUT-system bus interface and, possibly, a specific imitator of an external device. Different devices with one programming interface can be tested by the same test program even if they have different bus interfaces; different bus interfaces require different adapters to be implemented. The presented approach gives an opportunity to use the same test program both for standalone and for system-level verification (as an integration test). The implementation of the presented approach and its application to verification of microprocessors of the Elbrus family are described.